2020
DOI: 10.1002/aenm.202002753
|View full text |Cite
|
Sign up to set email alerts
|

MnN4 Oxygen Reduction Electrocatalyst: Operando Investigation of Active Sites and High Performance in Zinc–Air Battery

Abstract: The development of inexpensive and highly efficient nonprecious metal catalysts to substitute Pt in the alkaline oxygen reduction reaction is an appealing idea in the energy field. Herein, a Mn oxygen reduction electrocatalyst with a half‐wave potential (E1/2) as high as 0.910 V under an alkaline oxygen reduction reaction process is developed, and the dynamic atomic structure change of the highly efficient Mn single‐atomic site is investigated using operando X‐ray absorption spectroscopy. These results demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 49 publications
2
60
0
Order By: Relevance
“…The electrochemical tests showed that the Mn-based SACs had an excellent performance on ORR showing promising half-wave potential of 0.87 V and diffusion current-limiting performance of ZABs under alkaline conditions, which was superior to most Mn-based nanomaterial catalysts and Pt/C catalysts. More recently, well-dispersed Mn single-atoms anchored nitrogen-doped carbon with Mn–N 4 configuration catalyst (Mn-SAS/CN) was prepared by one-step thermal activation of Mn(CH 3 COO) 2 @ZIF-8 precursor [ 114 ]. The operando X-ray absorption spectroscopy analysis showed that the active sites of Mn changed with the applied potential under the basic ORR condition, and Mn L+ –N 4 without covering OH ads was the catalytic center.…”
Section: Mof-derived Oxygen Electrocatalysts As Air Electrode In Zabsmentioning
confidence: 99%
“…The electrochemical tests showed that the Mn-based SACs had an excellent performance on ORR showing promising half-wave potential of 0.87 V and diffusion current-limiting performance of ZABs under alkaline conditions, which was superior to most Mn-based nanomaterial catalysts and Pt/C catalysts. More recently, well-dispersed Mn single-atoms anchored nitrogen-doped carbon with Mn–N 4 configuration catalyst (Mn-SAS/CN) was prepared by one-step thermal activation of Mn(CH 3 COO) 2 @ZIF-8 precursor [ 114 ]. The operando X-ray absorption spectroscopy analysis showed that the active sites of Mn changed with the applied potential under the basic ORR condition, and Mn L+ –N 4 without covering OH ads was the catalytic center.…”
Section: Mof-derived Oxygen Electrocatalysts As Air Electrode In Zabsmentioning
confidence: 99%
“…The residual Mn was verified to be not the major ORR active sites by the SCN − poisoning experiment (Figure S12, Supporting Information). [ 31 ] In addition, the effect of pyrolysis time on the structure and ORR performance of N‐NPC‐900 sample was also investigated (Figure S13, Supporting Information). The ORR catalytic activity of N‐NPC samples was analyzed by double‐layer capacitance ( C dl ) values, electrochemical impedance spectroscopy (EIS), and N‐dopant concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Han et al [ 28 ] developed Mn Single Atom Site catalysts on N‐doped Carbon supports (Mn‐SAS/CN) via single stage pyrolysis, yielding NPs with dodecahedral morphologies (Figure 8e). EDX mappings in Figure 8f illustrate uniform Mn (green), C (blue), and N (red) distributions over whole Mn‐SAS/CN surfaces, while AC HAADF‐STEM confirm Mn isolation via circled (red) bright dots (Figure 8g).…”
Section: Engineering Morphology To Tune Catalytic Propertiesmentioning
confidence: 99%
“…Further, Han et al [ 28 ] studied the active sites of Mn‐N 4 for oxygen reduction. More directly, dynamic and reversible modulation of Mn active center valences from higher (Mn H+ ‐N 4 ) to lower (Mn L+ ‐N 4 ) charges can responsively tune OH coverage in ORR and related reactions.…”
Section: The Impact Of Composition On Experimental Characterizationmentioning
confidence: 99%
See 1 more Smart Citation